Perancangan Komik Digital sebagai Eksplorasi Visual Dampak dari Tawuran - Gunawan, Dominikus Donny; Sari, Yulianti Mayank (Universitas Pembangunan Jaya, 2023)
Brawls in Indonesia, traditionally stemming from the student community, have evolved into a troubling phenomenon, raising concerns about the nation's future generations. To address this issue, the author undertakes a thorough analysis of the underlying causes that contribute to these brawls, aiming to formulate effective solutions as an alternative approach to handling the situation. This analytical process serves as a critical foundation for devising a comprehensive strategy. As part of the proposed solution, the author explores the potential of utilizing visual and persuasive elements, specifically through the creation of a comic medium. Comics are recognized as a powerful and accessible means of conveying messages that are not only engaging but also easily comprehensible across diverse segments of society. The objective is to develop a comic that serves not only as entertainment but also as an educational tool, providing a profound understanding of the consequences of conflicts. Through this approach, the intention is to impart valuable lessons and foster positive awareness, particularly among the younger generation, contributing to a more harmonious and informed society.